2017
DOI: 10.3390/ijms18071565
|View full text |Cite
|
Sign up to set email alerts
|

Coconut Oil Aggravates Pressure Overload-Induced Cardiomyopathy without Inducing Obesity, Systemic Insulin Resistance, or Cardiac Steatosis

Abstract: Studies evaluating the effects of high-saturated fat diets on cardiac function are most often confounded by diet-induced obesity and by systemic insulin resistance. We evaluated whether coconut oil, containing C12:0 and C14:0 as main fatty acids, aggravates pressure overload-induced cardiomyopathy induced by transverse aortic constriction (TAC) in C57BL/6 mice. Mortality rate after TAC was higher (p < 0.05) in 0.2% cholesterol 10% coconut oil diet-fed mice than in standard chow-fed mice (hazard ratio 2.32, 95%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 46 publications
1
28
0
Order By: Relevance
“…To induce pressure overload, the TAC procedure was executed as described before (Muthuramu et al, ). Briefly, anaesthesia was induced with a single i.p.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To induce pressure overload, the TAC procedure was executed as described before (Muthuramu et al, ). Briefly, anaesthesia was induced with a single i.p.…”
Section: Methodsmentioning
confidence: 99%
“…Invasive haemodynamic measurements were performed 56 or 65 days after TAC or after sham operation as described previously (Muthuramu et al, ). Mice were anaesthetized by i.p.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Muthuramu et al. demonstrated that coconut oil containing rich GML aggravated pressure overload‐induced cardiomyopathy . However, it remained unknown whether GML produces any effect on metabolic syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…In this experiment, we not only added 1% cholesterol but also 5% coconut oil in the diet because coconut oil normally enhances cholesterol and LDL to a greater extent than cholesterol alone, as reported previously [63]. Moreover, coconut oil decreases myocardial capillary density and aggravates cardiomyopathy [64]. Thus 1% cholesterol with 5% coconut oil diet was sufficient to make the rats hypercholesterolemic in this study.…”
Section: Discussionmentioning
confidence: 66%